Indigenous Knowledge and HIV/AIDS : Ghana and Zambia - Naur, Maja (World Bank, Washington, DC, 2012)
The note reviews the cultural role of traditional healers in communities in Ghana, and Zambia, as one of the best hopes for treating, and stemming the spread of AIDS. However, healers rely on medicinal plants which have significantly decreased, as their habitats are lost through deforestation, cultivation, overgrazing, burning droughts, and desertification among others. This has been exacerbated by poor management of local, and international demand for medicinal plants, and by the identification by traditional healers, of the loss of indigenous knowledge regarding traditional medicine, which is part of the cultural heritage of local communities, usually transmitted orally. Based on the importance to preserve this ethno-medical knowledge, with the support of the World Bank, the governments of these two countries aim at establishing a bridge between environment, and health in fighting HIV/AIDS, through the Environmental Support Program in Zambia, and the Northern Savanna Biodiversity Conservation Project in Ghana. The note describes the AIDS components, involving traditional healers, and compares socio-cultural findings, particularly concerning gender differences related to traditional medicine. Although gradual, this approach is benefiting the poor directly, with considerable potential in treating AIDS-related diseases.